Pengaruh Kondisi Keuangan, Ukuran Perusahaan Dan Provibilitas Terhadap Penerimaan Opini Audit Going Concern Perusahaan Manufaktur Food And Beverage - Ni Wayan Putri Darmayanti; Baiq Kisnawati; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
Public companies in Indonesia have experienced rapid development. This growth has led to an increasing demand for company financial reports. Investment decisions have become more challenging and uncertain for investors due to the outbreak of the coronavirus around the year 2019. The COVID-19 pandemic has not only impacted public health but also affected the country's economy, education, and social life in Indonesia. The food & beverage industry is one of the sectors that has been severely affected by this pandemic. Various factors contribute to companies receiving going concern audit opinions from auditors, such as financial conditions, company size, and profitability. The research method used in this study is a quantitative approach, and data analysis techniques include descriptive statistical analysis and logistic regression analysis. The population in this research consists of 30 food and beverage companies that have gone public and have been listed on the Indonesia Stock Exchange (IDX) during the years 2019 to 2022. The research findings indicate that the variables of financial conditions, company size, and profitability have respective significance values of 0.008, 0.008, and 0.011. This means that each variable has a dominant partial influence on going concern audit opinions